2019
DOI: 10.1038/s41374-018-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical approach to detect oncogenic CTNNB1 mutations in primary neoplastic tissues

Abstract: The Wnt/β-catenin signaling pathway is dysregulated in different types of neoplasms including colorectal cancer (CRC). Aberrant activation of this signaling pathway is a key early event in the development of colorectal neoplasms, and is mainly caused by loss of function mutations in Adenomatous Polyposis Coli (APC), and less frequently by β-catenin stabilization mutations via missense or interstitial genomic deletions in CTNNB1. In this study, we have defined an immunohistochemical algorithm to dissect Wnt pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 30 publications
(33 reference statements)
1
11
0
Order By: Relevance
“…With the advent of genomics, molecular or genetic variants affecting disease risk can be identified (Field, 2008). Mutations in the gene encoding b-catenin (CTNNB1) have been detected in numerous human malignancies, including lung cancer (Woenckhaus et al, 2008), malignant mesothelioma (Shigemitsu et al, 2001), desmoid tumors (Colombo et al, 2013), colon cancer (Akyol et al, 2019), and others. Woenckhaus et al (2008) identified a number of differentially expressed genes in smoke-exposed bronchial epithelium and nonsmall cell lung cancers (NSCLCs), they found in adenocarcinomas, the cytoplasmic expression of beta-catenin was associated with shorter survival (p = 0.012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of genomics, molecular or genetic variants affecting disease risk can be identified (Field, 2008). Mutations in the gene encoding b-catenin (CTNNB1) have been detected in numerous human malignancies, including lung cancer (Woenckhaus et al, 2008), malignant mesothelioma (Shigemitsu et al, 2001), desmoid tumors (Colombo et al, 2013), colon cancer (Akyol et al, 2019), and others. Woenckhaus et al (2008) identified a number of differentially expressed genes in smoke-exposed bronchial epithelium and nonsmall cell lung cancers (NSCLCs), they found in adenocarcinomas, the cytoplasmic expression of beta-catenin was associated with shorter survival (p = 0.012).…”
Section: Introductionmentioning
confidence: 99%
“…Shigemitsu et al (2001) found CTNNB1 is infrequently mutated in lung cancer. Akyol et al (2019) defined an immunohistochemical algorithm to dissect Wnt pathway alterations in formalin-fixed and paraffin-embedded neoplastic tissues and found all six colon adenomas of the 126 total adenomas studied for the altered/ mutant b-catenin staining pattern had presumptively pathogenic point mutations or deletions in CTNNB1. The N-terminus of b-catenin, with contains conserved phosphorylated threonine/ serine amino acid residues, is the most frequent location of cancer-related CTNNB1 mutations (Dar et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,16 Hence, accumulation of clinicopathological evidences regarding the mutant cells and their localisation in normal epithelium is essential. However, it is currently difficult to detect mutant cells histopathologically in situ, because mutations leading to the expression of aberrant proteins that can be detected immunohistochemically are limited for genes such as TP53, 17 CTNNB1, 18,19 ARID1A, 20,21 SMARCB1, 22 SMARCA4, 23 IDH1, 24 and BRAF. 25 Clonal expansion of epithelial cells harbouring oncogenic mutations in the female genital tract was documented prior to the NGS era.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent issue of Laboratory Investigation, Akyol et al describe an immunohistochemical approach to detect oncogenic CTNNB1 mutations in primary neoplastic tissues [1]. The β-catenin signaling pathway is one of the most commonly deregulated pathways among various types of cancers [2].…”
mentioning
confidence: 99%